Gambaran Penerimaan Diri Remaja Yatim Piatu di Panti Asuhan : Sebuah Literature Review - I Dewa Agung Gede Wahyu Raditya Ardana; B. Primandini Yunanda Harumi (JURNAL RISET RUMPUN ILMU PENDIDIKAN, 2025)
Individuals who do not live with their parents or do not have a nuclear family are generally placed in social care institutions such as orphanages. Living outside the family environment causes orphaned adolescents to experience limitations in building emotional bonds that are usually obtained from interactions with family. The absence of strong emotional relationships can affect various aspects of adolescent psychology, one of which is self-acceptance. Adolescents living in orphanages often perceive themselves as different from adolescents raised in intact families. This feeling can impact the formation of self-concept, self-esteem, and how they view and accept themselves. This study aims to examine the level of self-acceptance of orphaned adolescents living in orphanages, identify factors that influence self-acceptance, and understand the role of self-acceptance in relation to other psychological variables. This study was conducted using a literature review method of various relevant previous research results. Based on the results of the literature review, it was found that self-acceptance of orphaned adolescents in orphanages is generally at a moderate to high level. Several key factors contributing to this self-acceptance include social support from the surrounding environment, self-esteem, optimism, and a positive self-concept. These factors are interrelated and play a crucial role in shaping the psychological resilience and mental health of adolescents in orphanages.   Keywords: self-acceptance , orphaned teenager, orphanage